Augmented and virtual reality : First international conference, AVR 2014, Lecce, Italy, September 17-20, 2014, Revised Selected Papers - Mongelli, Antonio; De Paolis, Lucio Tommaso (Lecture Notes in Computer Science, 2014)
This book constitutes the thoroughly revised papers of the First International Conference on Augmented and Virtual Reality, AVR 2014, held in Lecce, Italy, in September 2014. The 28 papers, 2 tutorials and 3 keynotes presented were carefully reviewed and selected from 76 submissions. They include topics from virtual/augmented/mixed reality to 3D user interfaces and the technology needed to enable these environments to a wide range of applications (medical, entertainment, military, design, manufacture, maintenance, arts and cultural heritage).